Monocarboxylate Transporter 8 Modulates the Viability and Invasive Capacity of Human Placental Cells and Fetoplacental Growth in Mice - Vasilopoulou, Elisavet (Public Library of Science, 2013)
Monocarboxylate transporter 8 (MCT8) is a well-established thyroid hormone (TH) transporter. In humans, MCT8 mutations result in changes in circulating TH concentrations and X-linked severe global neurodevelopmental delay. MCT8 is expressed in the human placenta throughout gestation, with increased expression in trophoblast cells from growth-restricted pregnancies. We postulate that MCT8 plays an important role in placental development and transplacental TH transport. We investigated the effect of altering MCT8 expression in human trophoblast in vitro and in a Mct8 knockout mouse model. Silencing of endogenous MCT8 reduced T3 uptake into human extravillous trophoblast-like cells (SGHPL-4; 40%, P<0.05) and primary cytotrophoblast (15%, P<0.05). MCT8 over-expression transiently increased T3 uptake (SGHPL-4∶30%, P<0.05; cytotrophoblast: 15%, P<0.05). Silencing MCT8 did not significantly affect SGHPL-4 invasion, but with MCT8 over-expression T3 treatment promoted invasion compared with no T3 (3.3-fold; P<0.05). Furthermore, MCT8 silencing increased cytotrophoblast viability (∼20%, P<0.05) and MCT8 over-expression reduced cytotrophoblast viability independently of T3 (∼20%, P<0.05). In vivo, Mct8 knockout reduced fetal:placental weight ratios compared with wild-type controls at gestational day 18 (25%, P<0.05) but absolute fetal and placental weights were not significantly different. The volume fraction of the labyrinthine zone of the placenta, which facilitates maternal-fetal exchange, was reduced in Mct8 knockout placentae (10%, P<0.05). However, there was no effect on mouse placental cell proliferation in vivo. We conclude that MCT8 makes a significant contribution to T3 uptake into human trophoblast cells and has a role in modulating human trophoblast cell invasion and viability. In mice, Mct8 knockout has subtle effects upon fetoplacental growth and does not significantly affect placental cell viability probably due to compensatory mechanisms in vivo.